Efficacy of Opioid-Free Anesthesia vs Opioid Anesthesia in Postoperative Outcome of Patients Underwent General Anesthesia - Ananda, Pratama; Anggraeni, Novita; Sari, Valencia Ayu (Journal of Anaesthesia and Pain, 2025)
Background: Opioids are widely used narcotic analgesics in perioperative settings. However, it has a series of postoperative side effects. Opioid-free anesthesia (OFA) is an anesthetic technique that avoids the use of opioids intraoperatively to minimize their side effects. This study aimed to compare the postoperative outcome and side effects between OFA and opioid anesthesia. Methods: This is a randomized comparative experimental study in adults undergoing elective surgery under general anesthesia. We enrolled 30 patients and divided them into Group A (treatment) (n = 15), who were given ketamine at 0.25-0.5 mg/kg repeated every 30 minutes and 2% lidocaine at 1-1.5 mg/kg followed by maintenance doses. Group B (control) (n = 15) received fentanyl at 1-5 µg/kg/hour. Postoperative outcome (pain intensity) using the Wong-Baker FACES® Pain Rating Scale and side effects of opioids, including postoperative hypoxia, ileus, delirium, and postoperative nausea and vomiting (PONV), were observed. The data between groups were analyzed using the Wilcoxon, chi-square, unpaired t-test, Fisher’s exact, and Mann-Whitney test with α = 0.05. Result: Moderate to severe postoperative pain was observed to be higher in the control group than in the treatment group (88.9% vs 11.1%) (p = 0.020). Incidence of hypoxia, ileus, delirium, nausea, and vomiting in group A (p = 0.003; p = 0.030; p = 0.042; p = 0.001, respectively) was higher compared to group B. Conclusion: The use of OFA results in better postoperative pain control and a lower incidence of postoperative opioid-related side effects, i.e., postoperative hypoxia, ileus, delirium, and PONV.